Impact Analysis from Implementation Payment Application - Boarding’s School Gontor in Order to Administration Efficiency - Zyk Farhad, Arisy; Nurul, Fadilah; Binti Sukari, Afaf (Jurnal Manajemen dan Inovasi (MANOVA), 2025)
Objective – This study aims to determine the implementation of the “Administrasi Gontor” application in facilitating PMDG Surabaya in payments and student needs and to determine the satisfaction of PMDG Surabaya student’s guardian on the “Administrasi Gontor” application.. Design/methodology/approach – The method applied in this research is descriptive qualitative method, this is because researchers want to look further into the problems in using the “Administrasi Gontor” application. Stages of data collection through non-structured interviews with quota sampling techniques, namely those selected in the study were the Surabaya student’s guardian coordinator with a total of 7 respondents Findings – The results indicate that the application significantly assisted guardians during pandemic restrictions. However, satisfaction among guardians in Surabaya remains moderate, with some expressing satisfaction while others reported critical issues. This highlights the need for improvements in management, regulations, and information related to cottage administration. Research limitations/implications – This research was only conducted in some student’s guardian of Gontor live at Surabaya. As a recommendation, the author suggests further study in the same nor other context of other City or country. Next suggest that further research can explore another object that can influence the construct of financing ecosystem in Gontor . Practical implications – This study emphasizes the importance of customer satisfaction in enhancing payment quality through the application. Customer satisfaction is crucial for mediating the relationship between an environmentally friendly brand image and loyalty, even with a single payment service. Additionally, companies should avoid greenwashing practices, particularly in highly religious countries, as this can undermine brand loyalty. Originality/value – This research examines customer satisfaction in order to develop payment gate with application "Administrasi Gontor". In addition, the renewal or originality of this research is in reviewing the usefulness of payment technology to support convenience in payment transactions or providing the needs of boarding school students. This study found that the needs of students can be met easily because there is a Gontor Administration application, as well as the payment of walisantri to the cottage is getting easier because of this. from that, transaction satisfaction and Guardian’s student boarding school trust in the Boarding school are increasing.